Thalassaemia in Vanuatu, south-west Pacific: frequency and haematological phenotypes of young children. - Ganczakowski, M; Bowden, D; Maitland, K; Williams, T; O'Shaughnessy, D; Viji, J; Lucassen, A; Clegg, J; Weatherall, D (1995)
The archipelago of Vanuatu situated in the South-West Pacific has a high frequency of alpha + thalassaemia and additionally on some of the islands there is a high frequency of beta thalassaemia. As part of a large cohort study to investigate the clinical effect of thalassaemia on malaria on the islands of Espiritu Santo and Maewo in Vanuatu, the gene frequencies of the thalassaemias were determined and blood counts were performed on a cohort of infants from birth to 3 years. The haematological phenotypes of the different thalassaemic genotypes are compared, providing a detailed description of the clinical manifestations of alpha + thalassaemia during early development. In addition, cross-sectional surveys of the population of the two islands were performed to establish the frequency of thalassaemia and other red cell polymorphisms and their geographical distribution.